2006
DOI: 10.1517/14712598.6.7.671
|View full text |Cite
|
Sign up to set email alerts
|

The tumour microenvironment and implications for cancer immunotherapy

Abstract: Tumour cells exist in a complex milieu of cellular and non-cellular components comprising fibroblasts, endothelial cells, immune cells and metabolites of cellular respiration. An elaborate interplay between these components and tumour cells exists with implications for immunological recognition of tumour cells. Tumours have been shown to alter their antigen and cytokine profiles, desensitise and impair immune defences, signal fibroblasts to facilitate metastasis, and take advantage of acidic and hypoxic condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 106 publications
0
20
0
Order By: Relevance
“…Moreover, tumor cells themselves play a crucial role in controlling the antitumor immune response (5), allowing them to maintain their functional disorder and evade destruction by CTLs. In this regard, it has been suggested that tumor cell growth in vivo is not only influenced by CTL-tumor cell recognition (6) and tumor susceptibility to cell-mediated death, but also by the complex and highly dynamic tumor microenvironment, providing very important clues to tumor development and progression (7).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, tumor cells themselves play a crucial role in controlling the antitumor immune response (5), allowing them to maintain their functional disorder and evade destruction by CTLs. In this regard, it has been suggested that tumor cell growth in vivo is not only influenced by CTL-tumor cell recognition (6) and tumor susceptibility to cell-mediated death, but also by the complex and highly dynamic tumor microenvironment, providing very important clues to tumor development and progression (7).…”
Section: Introductionmentioning
confidence: 99%
“…6 In addition, the tumor microenvironment has to be conducive to immune cell function. 7 In normal immune responses to microorganisms, appropriate signals (danger signals) are produced that result in the localized production of chemokines and cytokines. 8 Instrumental in this process are resident dendritic cells (DC) that respond to ligation of Toll-like receptors (TLR) by pathogen-associated molecular patterns present on microbial products.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] During cancer progression, cancer cell interactions with the ECM are crucial for tumor growth, metastasis and responses to antitumor therapy. 5,9 Moreover, angiogenesis plays a critical role in tumor growth. 10,11 Thus, the stroma tightly controls cancer cell behavior.…”
mentioning
confidence: 99%